Meningkatkan Hasil Belajar Pada Siswa Kelas II SDIT Ar Risalah Secang Melalui Classroom Reading Program - Ilmiahwati,, Tibta (Prosiding University Research Colloquium, 2021)
The study aims to determine the increase in learning outcomes from the implementation of the classroom reading program. The approuch used in this a qualittative approach with the type of classroom actionresearch. Research location at SDIT Ar Risalah Secang with the subjectof class II student who do not amount to 20 siswa. Data collection techniques used are tests and observations. Based on the result of the analysis, it can be concluded that the improvement of learning outcomes using the classroom reading program in thematic learning in grade II students og SDIT Ar Risalah Secang. The author wishes to try to increase interest in readingg and learning outcomes throught action by implementing the classroom reading program.. The step of the classroom reading peogram are,1) holding a class library by involving children in managing the books in the library,2) using reading books as additional references in the learning process, 3) creating creative reading activities to produce what student have read. Clasically reading interest and learning outcomes increased from the initial conditions, the first activity, and the second activity, respectively by 30%,68%,and 75%. Clasically an increase in reading interest and student learning outcomes is achieved.